Surface integrity of mild steel in wire electrical discharge machining - Mohamad Suffi, Kamari (2010)
This project deals with machining Mild Steel work piece using Wire Electric Discharge Machine (WEDM). The objective of the project is to determine the surface integrity of material when machining with different parameters. In this particular project, five parameters are being used which are on time, off time, peak current, servo voltage and wire speeds. From the experiment, the surface roughness was measured using perthometer. The machining of Mild Steel work piece was performs using Wire-EDM Sodick AQ535L. Then, the analysis was done using the Statistica software. By doing this project using WEDM for mild steel AISI 1020, it will aid people to estimate the surface roughness for selected parameters and avoid using try and error method. From the analysis, on time and peak current are the significance parameters to the mild steel’s surface roughness. The lower value of on time and peak current used,, the result for surface roughness are better. By considers all of these parameters, the good machining condition can be performed.